Acquired Traumatic Diaphragmatic Hernia with Delayed Presentation in a Child - Nader Mutwakel Osman (Sudan Journal of Medical Sciences)
A congenital diaphragmatic hernia occurs because of embryologic defects in the diaphragm. Most patients with congenital diaphragmatic hernias present early rather than late in life, however, adults may present with a congenital hernia that was undetected during childhood. Acquired diaphragmatic hernias result from all types of trauma with blunt forces accounting for the majority [1]. The author reports a case of acquired diaphragmatic hernia in a three-year-old boy with a prolonged history of recurrent attacks of vomiting and abdominal pain associated with cough. After taking in to account the full history and investigation, it was proved to be a case of acquired diaphragmatic hernia.